2017
DOI: 10.1371/journal.pone.0184509
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional interventions for adolescents using information and communication technologies (ICTs): A systematic review

Abstract: A cost-effective and interactive way of promoting healthy nutrition behaviors among adolescents is using information and communication technologies (ICTs). We systematically reviewed studies to identify technologies and their main characteristics used for nutritional interventions for adolescents, as well as to evaluate their quality and effectiveness. Our full protocol is available on the PROSPERO website (#CRD42016035882). A search was conducted across five databases for articles describing nutritional inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 30 publications
1
30
0
3
Order By: Relevance
“…Few gamebased interventions have been created for such purpose. As innovative media, digital games are potentially capable of influencing health outcomes, providing engagement and pleasure (18,32,33) .…”
Section: Discussionmentioning
confidence: 99%
“…Few gamebased interventions have been created for such purpose. As innovative media, digital games are potentially capable of influencing health outcomes, providing engagement and pleasure (18,32,33) .…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews that did not focus on low-income groups reported greater effectiveness of nutritional interventions on the quality of the diet. Thus, in a review evaluating nutritional interventions by Information and Communications Technologies (ICT) on adolescents from high-income countries [ 39 ], the authors found that most interventions reported being effective in promoting nutrition-related health benefits. These results match those reported in previous reviews targeting children and adolescents not focused on low-income groups [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review pointed out that nutritional interventions based on theoretical models are more effective in establishing new health behaviours among adolescents. 7 The transtheoretical model stands out as a way of enhancing the effects of behavioural interventions. This theory proposes that behavioural change occurs over time and is mediated by four dimensions: stages of change, processes of change, self-efficacy and decisional balance.…”
Section: Introductionmentioning
confidence: 99%